A functional model of team leadership for sport - Coleman, J.; Tenenbaum. G. (Studies in Sport Humanities, 2017)
The purpose of this study was to propose and examine a new leadership framework, the Team Leadership Model for Sport. Specifi cally, the aim was to examine a functional leadership paradigm in sport where full range of leadership behaviors by the coach and by the collective athletes infl uence team cohesion, and thereby increase the likelihood of team goal achievement. Data were utilized from 518 NCAA Division I-III athletes from 36 softball teams and 13 baseball teams. The participants completed the Multifactor Leadership Questionnaire (Avolio & Bass, 2004), the Team Multifactor Leadership Questionnaire (Avolio & Bass, 1996), the Group Environment Questionnaire (Carron, Brawley, & Widmeyer, 1985), and the Team Outcome Questionnaire that was developed for this study. Structural equation modeling indicated that the original hypothesized model did not fi t the data, but an acceptable alternative model was established, which included transformational leadership and two transactional leadership variables infl uencing perceptions of cohesion. Transformational leadership had a signifi cant positive path to cohesion, which in turn had a signifi cant positive path to goal achievement. We discuss a potentially fruitful direction in the examination of team leadership, within which the fi rst step involves a closer examination of measurement of coach leadership, shared athlete leadership, and cohesion. Keywords: transformational, cohesion, shared leadership, baseball, softball